“Experimental Assessment Of Microstructure And Corrosion Properties Of Sg Iron (400/15 Grade) Under As-Cast And Nitrotec Treated Condition” - Ali, Sadique; Husain, Dr. Jakeer; Subhani, Dr. Amir Raza (Migration Letters, 2024)
Spheroidal Graphite (SG) iron castings (conforming to IS 400/15 grade) are made in green sand moulds. Test specimens are then machined from the castings. One set of Specimens is then subjected to Nitrotec Treatment, treating the surface with nitrogen atmosphere which resulted in the formation of Fe3N layer. The Nitrotec temperature selected is 5700C and 6300C. Specimen is held at this temperature for a fixed duration of 180 minutes and then quenched in quench bath (water based quenchant) maintained at 500C. The effect of Nitrotec Treatment on microstructure and corrosion is studied and compared with as-cast ones. The results of the research indicate the Graphite nodules are more or less uniform and distributed evenly in the ferritic matrix. The nodules count shows an average of 90 nodules/mm2. Corrosion or rusting is essentially a process of oxidation in which iron combines with water and oxygen to form rust, the reddish-brown crust that forms on the surface of the iron. Nitrotec treated specimen treated at 570º C exhibit lower corrosion rate compared with the ones treated at 630º C. This may be due to the higher hardness values obtained for low Nitrotec temperature treated ones. From the above investigation it is clear that the Nitrotec treatment has an effect on the microstructure and corrosion properties of SG iron castings leading to further investigation on Nitrotec treated SG iron by changing different parameters.